Sustainable Finance Initiatives In The Developing-8 Countries: Focus And Priorities In The Country Level - Jajang, Jajang (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2024)
This research aims to analyze the initiatives adopted by the D-8 countries in responding to the issue of sustainable finance. To achieve this goal, the research is designed using a qualitative literature review approach. In this research, data were obtained from the official websites of relevant national authorities, previous studies, and other reliable data sources. Research found that, at the organizational level, although there are no specific initiatives regarding sustainable finance, the initiatives taken have included sustainability dimensions, namely economic, social, and environmental dimensions. However, at the national level, each the D-8 countries have their own focus and priorities in responding to sustainable finance issues.Penelitian ini bertujuan untuk menganalisis inisiatif yang diambil oleh negara-negara D-8 dalam menanggapi isu keuangan berkelanjutan. Untuk mencapai tujuan tersebut, penelitian dirancang dengan menggunakan pendekatan tinjauan literatur kualitatif. Dalam penelitian ini, data diperoleh dari situs resmi otoritas nasional terkait, penelitian sebelumnya, dan sumber data lain yang dapat dipercaya. Penelitian menemukan bahwa, pada level organisasi, meskipun belum ada inisiatif khusus mengenai keuangan berkelanjutan, namun inisiatif yang diambil sudah mencakup dimensi keberlanjutan, yaitu dimensi ekonomi, sosial, dan lingkungan. Sedangkan di tingkat nasional, masing-masing negara D-8 mempunyai fokus dan prioritas masing-masing dalam menanggapi isu keuangan berkelanjutan.